Dose recommendations for anticancer drugs in patients with renal or hepatic impairment. Issue 4 (April 2019) - Krens, Stefanie D; Lassche, Gerben; Jansman, Frank G A; Desar, Ingrid M E; Lankheet, Nienke A G; Burger, David M; van Herpen, Carla M L; van Erp, Nielka P
Summary: Renal or hepatic impairment is a common comorbidity for patients with cancer either because of the disease itself, toxicity of previous anticancer treatments, or because of other factors affecting organ function, such as increased age. Because renal and hepatic function are among the main determinants of drug exposure, the pharmacokinetic profile might be altered for patients with cancer who have renal or hepatic impairment, necessitating dose adjustments. Most anticancer drugs are dosed near their maximum tolerated dose and are characterised by a narrow therapeutic index. Consequently, selecting an adequate dose for patients who have either hepatic or renal impairment, or both, is challenging and definitive recommendations on dose adjustments are scarce. In this Review, we discuss the effect of renal and hepatic impairment on the pharmacokinetics of anticancer drugs. To guide clinicians in selecting appropriate dose adjustments, information from available drug labels and from the published literature were combined to provide a practical set of recommendations for dose adjustments of 160 anticancer drugs for patients with hepatic and renal impairment.